DYNAMIC CHANGES OF TISSUE ENZYMES AND THE ITS INFLUENCE ON WOUND HEALING OF NASAL MUCOSA IN THE POSTOPERATIVE PERIOD - Marianna A. Zavalii; Aleksey N. Orel; Tatianna A. Krylova; Denis M. Kedrovskiy; Dilyana Vicheva (Peytchinski Publishing, 2022)
Intranasal surgery is widely spread all over the world and has the leading position among all otorhinolaryngological surgical interventions. However, any surgery makes sensitive trauma to the ciliaryepithelium that covers the nasal cavity and paranasal sinuses despite the modern technics of operations. That's why reveling peculiarities, patterns and ways of correction of nasal mucosa regeneration in the postoperative period is very important for clinicians. So the main aim of our paper is to investigate the role of some tissue enzymes in the process of nasal mucosa regeneration after surgical interventions on the structures of the nasal cavity in adults. As a result of our investigation, the role of some tissue enzymes was shown. We have based the usage of drugs that influence wound healing. Thus, the proper medicines have positive effects on the regeneration processes of the ciliated epithelium. A more thorough investigation of the role of these enzymes will allow developing methods of its correction for improving the efficiency of endonasal surgery rapid and qualitative recovery of mucociliary clearance.